2020
DOI: 10.1002/cncr.33191
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced coping and self‐efficacy in caregivers of stem cell transplant recipients: Identifying mechanisms of a multimodal psychosocial intervention

Abstract: BACKGROUND: In a recent trial, a 6-session intervention (BMT-CARE) integrating medical information with cognitive-behavioral strategies improved quality of life (QOL), mood, coping skills, and self-efficacy for family/friend caregivers of hematopoietic stem cell transplantation (HCT) recipients. This study examined whether improvements in coping and self-efficacy mediated the intervention effects on QOL and mood. METHODS: From December 2017 to April 2019, 100 caregivers of HCT recipients were enrolled into a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 32 publications
0
26
2
Order By: Relevance
“…Twenty‐four of the included articles reported RCTs while four studies used a quasi‐experimental design to assess the effect of PEIs on caregiver outcomes 15,34–36 . The majority of the trials were conducted in the United States of America 37–46 with just one trial from France, 47 Nigeria, 36 and Taiwan 35 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐four of the included articles reported RCTs while four studies used a quasi‐experimental design to assess the effect of PEIs on caregiver outcomes 15,34–36 . The majority of the trials were conducted in the United States of America 37–46 with just one trial from France, 47 Nigeria, 36 and Taiwan 35 …”
Section: Resultsmentioning
confidence: 99%
“…Other interventions were facilitated by social workers, 34,37,44,46,50 psychologists, 15,34,56,58 oncology experts 38 and three studies were facilitated by trained researchers 55,57,60 . The PEIs in 14 of the included trials was guided by a conceptual framework, 35,37,39,41,45,46,50,53,55,60,62,63 the most common being the Transactional Model of Stress and Coping 35,36,46,53 …”
Section: Resultsmentioning
confidence: 99%
“…Cancer patients with high self-efficacy expectations focus more on the demands of stressful situations and feel more efficacious in their ability in coping with changes and challenges resulting from cancer, which can promote better psychological adjustment and higher levels of resilience (Freire et al, 2020). Studies on cancer patients supported that a higher level of self-efficacy was associated with more self-care behaviours and positive coping strategies, such as relaxation, cognitive restructuring, and assertive communication (Johansson et al, 2018;Chou, 2019;Jacobs et al, 2020). It has been found that as the positive coping strategies increased, psychosocial adjustment also improved, which add to increased resilience (Yu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A newly published study investigated the effectiveness of an individual six-session psychosocial intervention for family caregivers in autologous and allogeneic HSCT care, where improved QoL, self-efficacy, and coping skills reduced caregiving burden, lower anxiety, and depression symptoms in comparison with a group that received standard care were reported (El-Jawahri et al, 2020). Coping and self-efficacy have been shown to be essential components of a brief psychosocial intervention that improves QoL and mood for caregivers of HSCT recipients during the acute recovery period (Jacobs et al, 2020).…”
Section: Discussionmentioning
confidence: 99%